2001
DOI: 10.1093/hmg/10.13.1387
|View full text |Cite
|
Sign up to set email alerts
|

Recombination hotspot in NF1 microdeletion patients

Abstract: Neurofibromatosis type 1 (NF1) patients that are heterozygous for an NF1 microdeletion are remarkable for an early age at onset and an excessive burden of dermal neurofibromas. Microdeletions are predominantly maternal in origin and arise by unequal crossover between misaligned NF1REP paralogous sequence blocks which flank the NF1 gene. We mapped and sequenced the breakpoints in several patients and designed primers within each paralog to specifically amplify a 3.4 kb deletion junction fragment. This assay amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
143
3

Year Published

2004
2004
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(150 citation statements)
references
References 28 publications
4
143
3
Order By: Relevance
“…All seven microduplications span the entire NF1 gene; five of the microduplications may represent the reciprocal duplication of the more common 1.4-Mb type 1 or 1.2-Mb type 2 NF1 microdeletion resulting from NAHR between NF1-REP A and NF1-REP C or its neighboring sequence. 10,13 The microduplication in subject 4 is likely reciprocal to the 1.0-Mb type 3 NF1 microdeletion, caused by NAHR between NF1-REP B and NF1-REP C; 11 subject 3's microduplication was detected on a targeted bacterial artificial chromosome array that could not distinguish between these duplication types. All seven duplications were visualized by FISH (Figure 2).…”
Section: Results Molecular Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…All seven microduplications span the entire NF1 gene; five of the microduplications may represent the reciprocal duplication of the more common 1.4-Mb type 1 or 1.2-Mb type 2 NF1 microdeletion resulting from NAHR between NF1-REP A and NF1-REP C or its neighboring sequence. 10,13 The microduplication in subject 4 is likely reciprocal to the 1.0-Mb type 3 NF1 microdeletion, caused by NAHR between NF1-REP B and NF1-REP C; 11 subject 3's microduplication was detected on a targeted bacterial artificial chromosome array that could not distinguish between these duplication types. All seven duplications were visualized by FISH (Figure 2).…”
Section: Results Molecular Analysismentioning
confidence: 99%
“…7 The deletions may be 1.0-1.4 Mb in size depending on the specific LCR mediating the deletion and are classified as types 1-3. [6][7][8][9][10][11] The most common NF1 microdeletion, type 1, is a 1.4-Mb deletion mediated by LCRs NF1-repeat (-REP) A and NF1-REP C (Figure 1) and is hypothesized to preferentially arise during meiotic NAHR. 8 Type 2 microdeletions have predominantly been seen as a result of mitotic NAHR and are 1.2 Mb in size with breakpoints within SUZ12 and its pseudogene SUZ12P adjacent to NF1-REP C and NF1-REP A, respectively (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…The type-1 deletions in the respective patients were confirmed by two independent methods: FISH (fluorescent in situ hybridization) and breakpoint junction PCR to amplify across the recurrent breakpoints, PRS1 and PRS2. The methodology and primer pairs used to amplify across PRS2 were as described by Lopez-Correa et al, 27 while primer pairs used to amplify across PRS1 were reported by Forbes et al 30 The parents of patients with type-1 deletions (and breakpoints in either PRS1 or PRS2) investigated in this study are listed in Data analysis was accomplished by exporting the peak area to an Excel file. The relative probe signal was then determined by a normalization procedure as described.…”
Section: Dna Samples From Patients and Their Parentsmentioning
confidence: 99%
“…Two distinct types of recurrent NF1 gene deletion have been documented: the first of these, type-1 deletions, span 1.4 Mb and are characterized by breakpoints, which cluster within the NF1-REPs in two regions, B15 kb apart, termed PRS1 and PRS2 (paralogous recombination sites 1 and 2). 27,30,31 By contrast, type-2 NF1 deletions encompass 1.2 Mb with breakpoints in the SUZ12 gene and its pseudogene both of which are located in close proximity to the NF1-REPs (Figure 1). 32 -34 Less frequent than the type-1 and type-2 deletions are the so-called atypical NF1 deletions with non-recurring breakpoints.…”
Section: Introductionmentioning
confidence: 99%
“…Sample sNF94.3 cells do not have p53 loss of heterozygosity but showed a constitutional NF1 mutation, which is a microdeletion of the common 1.4 Mb type with breakpoints in the NFREPs and was detected using PCR (Dorschner et al, 2000;Lopez- …”
Section: Phenotypic and Genetic Characterization Of The Snf943 Cell mentioning
confidence: 99%